2011
DOI: 10.4284/0038-4038-78.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Military Conscription and the (Socially) Optimal Number of Boots on the Ground

Abstract: In this article, we develop a model of military manpower mobilization. We use the model to evaluate the efficacy of volunteer‐ and conscription‐based manpower systems within a framework of social welfare maximization. We find that neither conscription nor a volunteer approach is likely to be “first best” because of asymmetries of information and constraints on the military pay structure. We then modify the general model by considering the possibility that recruits with high civilian productivity are also more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…First, since the military does not have to pay a premium for drafting high-ability individuals, it is unlikely that the draft would balance a draftee's productivity while in the military with the opportunity cost of pulling him or her out of the civilian labour market. The individuals selected for military service would be overly skilled (see Berck and Lipow 2011). Second, conscripts will form the main recruitment pool for the professional branch of the Swedish Armed Forces.…”
Section: Discussionmentioning
confidence: 99%
“…First, since the military does not have to pay a premium for drafting high-ability individuals, it is unlikely that the draft would balance a draftee's productivity while in the military with the opportunity cost of pulling him or her out of the civilian labour market. The individuals selected for military service would be overly skilled (see Berck and Lipow 2011). Second, conscripts will form the main recruitment pool for the professional branch of the Swedish Armed Forces.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, if h < .5, then z would be declining as a result of the incremental increase in w. Should h be greater than .5, then the average aptitude of recruits would monotonically increase with the wage. Now, we continue the analysis by following Berck and Lipow (2011) in assuming a function for the production of defense capability of form Q ¼ ðN zrÞ a . Using this function, we determine the value of w, w ⁄ , that provides the desired levels of capability at minimum cost.…”
Section: A Model Of Volunteer Military Manpower Mobilizationmentioning
confidence: 99%
“…Recent papers in this literature include , Berck and Lipow (2011), Simon (2011), andPerri (2012). Excellent reviews of earlier research on this subject can be found in Williams and Gilroy (2006) and Asch, Hosek, and Warner (2007).…”
Section: Introductionmentioning
confidence: 99%
“…The first is the DWL of taxation, which applies only to the volunteer system and has played a prominent role in the extant comparison of the two employment systems (Lee and Mckenzie, 1992;Ross, 1994;Warner and Asch, 1996). The second cost affects the draft system by allowing for slow-going or lower productivity among draftees (Berck and Lipow, 2011).…”
Section: System-specific Costsmentioning
confidence: 99%